Structural insights on P31‐43, a gliadin peptide able to promote an innate but not an adaptive response in celiac disease. (25th March 2019) - Calvanese, Luisa; Nanayakkara, Merlin; Aitoro, Rosita; Sanseverino, Marina; Tornesello, Anna Lucia; Falcigno, Lucia; D'Auria, Gabriella; Barone, Maria Vittoria
Abstract : Inflammation of intestinal tissue in patients affected by celiac disease (CD) originates from the adaptive and innate immune responses elicited by the undigested gliadin fragments through molecular mechanisms not yet completely described. Undigested A‐gliadin peptide P31‐43 is central to CD pathogenesis, entering enterocytes in vesicular compartments by endocytosis and inducing an innate immune response in CD intestinal mucosa. This study focused on the reasons why P31‐43 does not behave as adaptive immunogenic agent. Once obtained by NMR analysis, the three‐dimensional model of P31‐43 was used to implement a series of in silico experiments aimed to explore the ability of the peptide to interact with HLA‐DQ2 and the corresponding receptor onto T cells. Our results show that P31‐43 is a poor ligand for DQ2 and/or T‐cell receptor. This study was also aimed to investigate, from a structural point of view, the previous experimental findings by which P31‐43 is able to enhance the phosphorylation level of the protein ERK2, while some P31‐43 Ala‐mutants decrease or totally inhibit that process. The molecular models of P31‐43, P31‐43 P36A, and F37A mutants were used for in silico docking experiments onto the ERK2 structure. The experiments support the hypothesis that P31‐43 F37A works as an ERK2 phosphorylation inhibitor because it binds to the ERK2 phosphorylation site. This study reports on the structural properties of so far never NMR characterized gliadin peptides relevant in CD and explores details about their mechanisms of action. Abstract : P31‐43 was structurally defined and tested for its ability to bind HLA‐DQ2 and T cell receptor, the proteins that gliadin fragments, active in the adaptive immunogenic route, are able to bind to. In silico docking experiments confirm that P31‐43 is a poor ligand for both molecular systems.